Securing ISW Masking Scheme Against Glitches - Takarabt, Sofiane; Ebrahimabadi, Mohammad; Bahrami, Javad; Guilley, Sylvain; Karimi, Naghmeh (My University, 2024)
Ishai-Sahai-Wagner (ISW) masking scheme has been proposed in literature to protect cryptographic circuitries against side-channel analysis attacks. Although provably secure from a theoretical standpoint, its hardware implementation may not be secure as such security proof holds true if the gates are only evaluated after all of their inputs are available, yet such requirement is not met in hardware as the gates are evaluated as soon as any single input of them is changed. This paper provides a repair for ISW to address its security concern and prevent the key recovery. Our method is based on inserting artificial delays and/or "refreshing" on some sensitive paths to ensure that the underlying combinational gates are evaluated in the order expected by the ISW rationale. We verify the security of our proposed structure by leakage detection. Our solution is called E-ISW standing for Enhanced-ISW.
IEEE Design Automation and Test in Europe (March 2024), Valencia, Spain